Criticalidade auto-organizada na emissão de óxido nitroso (N2O) do solo - SERAFIM, Maria das Vitórias Alexandre (2016)
Studies related to greenhouse gas emission behavior are very important to understand the global warming. In the last decades, investigations have been carried out to know how the main gases behave in the earth’s surface. Among them, great emphasis is given to nitrous oxide (N2O), because of its high heat capacity and its permanency time in the atmosphere. The emissions of N2O from the soil are highly variable, with a long range and this characteristic difficult the study of this gas, becoming the statistical inference of this measure a hard task. Before that, a series of empirical methods have been more and more used in the estimating emissions of the nitrous oxide from agricultural and forestry system. However, these methods do not appear adequate to explain the great variability observed in the values of N2O in terms of a probability density function, because of the conceptual form of these models. Besides, phenomena with the same characteristics of the nitrous oxide emissions of the soil were better described as critically self-organized system (SOC). So, it was directed to the question in order to find self-organized criticality evidence of N2O in different uses of the soil and in different environmental setting such as temperature changes. To answer the objectives of this work were broached some theoretical and practical results of the SOC idea and it was evaluated the behavior of the nitrous oxide emission in a natural rainforest soil, observing if the emissions show a SOC behavior both in a natural soil and when the same is heated. Also, SOC presence in the N2O emission of the soil in different lands uses, such as pasture and sugarcane, was investigated.